THE USE OF VIDEOS AND ITS EFFECTIVENESS IN ELT: A SYSTEMATIC REVIEW - Alfi Fithrotul ’Aini; Annisa Navira, Nita Noviyanti Rahayu, Siti Indah, Naf’an Torihoran (CV. ADIBA AISHA AMIRA, 2024)
Technology now controls almost all aspects of life, including ELT. One of them is the use of videos in learning, which has many benefits and obstacles. This article aims to determine the effectiveness of using video in ELT learning to improve students' abilities in listening, reading, writing, and speaking skills, as well as find out what obstacles occur during ELT learning using video technology. Qualitative analysis was used in this study, and systematic observation and meta-analysis (PRISMA) was the search strategy. Relevant data collection came from 3 databases, namely Google Scholar, ERIC, and Mendeley with several inclusion and exclusion criteria, resulting in 18 articles being studied. The research results show that using videos in ELT learning provides a positive perception because it can improve basic English language skills and increase self-confidence and motivation to learn. Apart from its effectiveness, there are also several inhibiting factors such as unstable internet, some students feeling uncomfortable, and audio problems when playing videos during learning